Neutrophyl – Lymphocyte Ratio (NLR) and C-Reactive Protein (CRP) Levels in Stable and Exacerbated Chronic Obstructive Pulmonary Disease (COPD) Patients in Persahabatan Hospital Jakarta - Astari Pranindya Sari; Ratnawati Ratnawati; Wahju Aniwidyaningsih; Sita Laksmi Andarini; Faisal Yunus (Respiratory Science, 2022)
Background: Although COPD has been believed to be characterized by respiratory disease, there are currently limited study conducted to evaluate inflammation markers and exacerbation rate in COPD by noninvasive methods. We did a prospective cohort study to observe the alteration of Neutrophyl-Lymphocyte Ratio (NLR) and C-reactive protein (CRP) in COPD patients to find any possible correlation with COPD exacerbation status. Method: From July to December 2018, a prospective cohort study was performed with blood and spirometry test on 31 COPD patients during exacerbation (AE-COPD) and stable. The mean of NLR and CRP were compared and analyzed. Results: Both NLR and CRP decreased during stable condition (from 7.95±6.8 to 4.6±5.5 and 43.4±71 to 12.2±18.5) with P<0.01 respectively. We also found a significant inverse correlation between NLR and FEV1/FVC in AE-COPD and CRP showed an inverse correlation only with FEV1 in AE-COPD. Another interesting finding was a subject with very high CRP whose value remained above the nomal limit during stable, and died within 2 months after exacerbation. Conclusion: NLR and CRP levels in COPD patients increased during exacerbation, which may reflect lung function and exacerbation status.